1996
DOI: 10.1111/j.1445-2197.1996.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Growth of Desmoid Tumours in Tissue Culture by Anti‐oestrogenic Substances: A Preliminary Report

Abstract: Background: Tamoxifen and toremifene have been used in patients with advanced desmoid tumours with response rates of 51%. Method:We developed an experimental model of desmoid tumour cells in tissue culture to study their effect. Four cell lines were established in tissue culture. All native and corresponding cultured tumours were oestrogen receptor negative. Tumour I was from a 22 year old with familial adenomatous polyposis (FAP) and recurrent abdominal wall desmoid turnours. She remains disease free on tamox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
1
20
0
2
Order By: Relevance
“…The use of tamoxifen has yielded the widest therapeutic experience. In a meta-analysis by Serpell et al, the response rate of 55 patients who were treated with antiestrogens was 51% [24]. Furthermore, Waddel has reported a 70% response rate with SERM in combination with nonsteroid anti-inflammatory drugs (NSAIDs) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The use of tamoxifen has yielded the widest therapeutic experience. In a meta-analysis by Serpell et al, the response rate of 55 patients who were treated with antiestrogens was 51% [24]. Furthermore, Waddel has reported a 70% response rate with SERM in combination with nonsteroid anti-inflammatory drugs (NSAIDs) [21].…”
Section: Discussionmentioning
confidence: 99%
“…L'evidenza che la mammella è un organo ormono-dipendente e che la fibromatosi extramammaria possa esprimere recettori estro-progestinici [37][38][39] e anche andare incontro a regressione, dopo trattamento con farmaci ad attività antiestrogenica [40], hanno fatto ipotizzare un'eziologia ormonale per la FM. Tuttavia, tutte le serie presenti in letteratura, compresa la presente, che hanno studiato il profilo recettoriale, non hanno evidenziato espressione di recettori estroprogestinici né di proteine regolate dagli estrogeni (ad esempio, la pS2), né infine di recettori per gli androgeni, rendendo dubbia un'eziologia ormonale e l'efficacia di una terapia anti-estrogenica [6,15,41].…”
Section: Discussioneunclassified
“…After the advent of immunohistochemistry in the 1980s, the majority of immunohistochemical analyses using antibodies raised against the ER contradicted these earlier studies [11][12][13] and, despite clinical findings which suggested a role for ER in the pathogenesis of desmoid tumors, it has been accepted that if estrogen had a role in fibromatosis, it was not by signaling through the ER pathway. 14,15 Although initial comparisons of immunohistochemical and biochemical assay methods found a good correlation between ligand binding and immunohistochemical techniques in breast carcinoma, no systematic comparison was made in mesenchymal lesions. 16 Because ligand binding assays assess binding of a radiolabeled or fluorescein-labeled ligand, this technique measures both ER␣ and ER␤.…”
Section: Discussionmentioning
confidence: 99%